(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Following the repressive policy of the “Cotton Case”, “Uzbek case”, which lasted from September 1983 to May 1989, the rights of thousands of Uzbeks were violated, the entire nation was blacklisted, the lives of the accused were destroyed, physically and morally humiliated. The article discusses the processes of liquidation of illegal investigative processes conducted in Uzbekistan.